A molybdenum isotope record of Eocene Thermal Maximum 2: Implications for global ocean redox during the early Eocene - Dickson, A; Cohen, A (2012)
During the early Eocene, a series of short-term global warming events ("hyperthermals") occurred in response to the rapid release of carbon into the oceans and atmosphere. In order to investigate the response of ocean redox to global warming, we have determined the molybdenum isotope compositions (δ98/95Mo) of samples spanning one such hyperthermal (Eocene Thermal Maximum 2 (ETM-2, 54.1 Ma)), from Integrated Ocean Drilling Program Expedition 302 Site M0004A in the Arctic Ocean. The highest δ 98/95Mo in our sample set (2.00 ± 0.11‰) corresponds to the development of local euxinia at Site M0004A during the peak of ETM-2, which we interpret as recording the global seawater δ98/95Mo at that time. The ETM-2 seawater δ98/95Mo is indistinguishable from a recent estimate of seawater δ98/95Mo from an earlier hyperthermal (Paleocene Eocene Thermal Maximum (PETM, 55.9 Ma), δ98/95Mo = 2.08 ± 0.11‰). We argue that the similarity in seawater δ98/95Mo during ETM-2 and the PETM was caused by the development of transient euxinia in the Arctic Ocean during each hyperthermal that allowed sediments accumulating in this basin to capture the long-term δ98/95Mo of early Eocene seawater. Our new data therefore place a minimum constraint on the magnitude of transient global seafloor deoxygenation during early Eocene hyperthermals. © 2012. American Geophysical Union. All Rights Reserved.